Anatomical Models versus Nontactile Distanced Learning in Otolaryngology Teaching - Pandya, Aashish; Mistry, Dylan; Owens, David (The Surgery Journal, 2021)
Introduction Medical schools in the United Kingdom are under increasing pressure to provide more streamlined, applicable teaching due to rising numbers of trainee doctors but are failing to meet their educational need for otolaryngology. The recent novel coronavirus disease 2019 (COVID-19) pandemic has placed additional pressures on medical schools to adapt the medium over which the curriculum is delivered. The use of tactile learning with three-dimensional models and distanced learning via videoconferencing may provide alternative teaching methods to meet otolaryngology undergraduate learning requirements. This pilot study aimed to assess the differences in undergraduate student attitudes toward tactile learning via nontactile distanced learning and review their acceptability among this cohort.Methods Two groups of medical students observed a single educational event on the larynx and management of the airway. The learning opportunity was delivered in a lecture format with the lecturer demonstrating on an anatomical model of the larynx. Group one (tactile group) had an identical model to interact with during the lecture and were present within the lecture theater; group two (nontactile group) did not and observed the lecture via video link. Students were asked to rank their opinion to several statements about the session based on an 11-point Likert's scale and give qualitative feedback.Results All ranked feedback was mainly positive. Tactile learning was statistically equivalent to nontactile learning based on the ranked feedback from the students, except for “improvement in anatomical knowledge,” for which the students believed tactile learning was superior (p = 0.017). A variety of qualitative feedback was received by both groups.Conclusion This pilot study provides evidence for the acceptability among students of the use of nontactile distanced learning to deliver the otolaryngology undergraduate curriculum compared with tactile learning. This can provide the basis for larger studies to assess the educational impact of these different teaching methods.
Keywords: medical education; anatomy; tactile learning; distanced learning; models; otolaryngology